Trend of Learning Media Model Create a Picture Story in Improving Children's Speaking Skills: Trend Media Pembelajaran Model Create a Picture Story Dalam Meningkatkan Keterampilan Berbicara Anak - Susanti, Dinik; Sudikan, Setya Yuwana; Hendratno, Hendratno (Madrosatuna: Journal of Islamic Elementary School, 2024)
Speaking skills are one of the important skills that children must have in the learning process. Video create a picture story is a learning media that uses sequential pictures accompanied by sound and text as a tool in the learning process. Previous research has shown that the use of audiovisual media can improve children's speaking skills. The literature study research shows a literature review that compares different audiovisual video media approaches in the use of speaking skills, such as narrative videos, animation, or augmented reality (AR). The literature study research method shows a literature review comparing various audiovisual video media approaches in the use of speaking skills. This research is expected to provide useful insights for the development of effective learning media in improving children's speaking skills. Increase the literature and understand the development of education and psychology in the field of effective and innovative learning media development. An interesting finding from the articles reviewed regarding interactive learning through pictures and videos is that audiovisual media based on Create a Picture Story provides more interactive and participatory learning. This finding shows that students taught using picture story-based video media have a higher level of information retention. Based on the results of the reviewed studies, it can be concluded that the use of Create a Picture Story videos in audiovisual media development has a significant effect on improving children's speaking skills. The learning model provides various benefits that support the development of speaking skills. The benefits include helping students organize ideas and compose sentences coherently, providing a context that makes it easier for students to understand and remember vocabulary and improve clarity of pronunciation.